2017
DOI: 10.1080/15384101.2017.1312236
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of ATM-deficient pancreatic cancer cells to radiation

Abstract: Ataxia telangiectasia mutated (ATM) is inactivated in a significant minority of pancreatic ductal adenocarcinomas and may be predictor of treatment response. We determined if ATM deficiency renders pancreatic cancer cells more sensitive to fractionated radiation or commonly used chemotherapeutics. ATM expression was knocked down in three pancreatic cancer cell lines using ATM-targeting shRNA. Isogenic cell lines were tested for sensitivity to several chemotherapeutic agents and radiation. DNA repair kinetics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…First, the pancreatic tumors of our mice have the genetic features of some aggressive forms of human pancreatic cancer, as it was shown that patients carrying tumoral loss of ATM and normal p53 expression tend to have very poor prognosis after tumor resection 42 . Second, the fact that our established ATM-deficient murine pancreatic tumor cells display radiosensitivity is quite relevant because other studies showed that human pancreatic tumor cells become radiosensitized upon treatment with an ATM inhibitor 43 or ATM siRNA 44 . Therefore, our mice are suitable models to test drugs or combined treatments that confer synthetic lethality (e.g., PARP1- or ATR inhibitors 45 , 46 ) to pancreatic tumors carrying ATM-deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…First, the pancreatic tumors of our mice have the genetic features of some aggressive forms of human pancreatic cancer, as it was shown that patients carrying tumoral loss of ATM and normal p53 expression tend to have very poor prognosis after tumor resection 42 . Second, the fact that our established ATM-deficient murine pancreatic tumor cells display radiosensitivity is quite relevant because other studies showed that human pancreatic tumor cells become radiosensitized upon treatment with an ATM inhibitor 43 or ATM siRNA 44 . Therefore, our mice are suitable models to test drugs or combined treatments that confer synthetic lethality (e.g., PARP1- or ATR inhibitors 45 , 46 ) to pancreatic tumors carrying ATM-deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, ataxia telangiectasia patients were found to be profoundly radiosensitive at the chromosomal level, suggesting the link between ATM and DNA repair (63). Preclinical data have demonstrated that knockdown of ATM results in radiosensitization (64,65). Additional studies in the laboratory have demonstrated that ATM alterations in malignant cells can sensitize cells to platinum drugs (44,66), and outside of platinum therapy, preclinical studies have also demonstrated ATM suppression in p53-deficient mouse fibroblasts sensitizes them to doxorubicin (67).…”
Section: Atm Deficiency: a Therapeutic Opportunity?mentioning
confidence: 99%
“…These combinations are rational because, as previously mentioned, ATM inhibitors have been shown to sensitize cells to PARP inhibitors, and also to both 5-FU and irinotecan (61,62,68). AZD1390, another oral ATM inhibitor that penetrates the blood-brain barrier, is currently being tested in combination with radiation, given that radiation has been demonstrated to be more effective in ATM-deficient cancers (65,79,80). Importantly, in considering the potential adverse events for this trial, knockout of ATM in healthy tissue as compared with cancerous tissue was shown to induce less radiation sensitivity (80).…”
Section: Atm Inhibitorsmentioning
confidence: 99%
“…A recent paper by Ayars et al [ 58 ] also showed that ATM-deficient PDAC cells were exquisitely sensitised to radiation, thus illustrating that ATM- mutated PDAC could be more sensitive to radiotherapy, and may thus provide more personalised treatment options for these patients in the future.…”
Section: The Role Of Different Mutations In Pdacmentioning
confidence: 99%